IMPACT OF CLIMATE CHANGE ON FOOD SECURITY IN NIGERIA: IS TERROR ATTACK A MATTER OF CONCERN? - MUSA, NUHU; MAJI, ALI; AJOGWU, IBRAHIM YUSUF (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Motivated by extreme weather events and incessant terrorist attacks in many parts of Nigeria with attendant consequences on agricultural output and food security challenges, this study was undertaken with a view to addressing the problem. Arising from the above, the objective of this study is to examine the impact of climate change and terrorism on food security in Nigeria using Autoregressive Distributed Lag (ARDL) method on time series data from 1990 to 2024. Food production index is regressed on temperature anomaly, carbon dioxide () emission and terrorism index. To improve the robustness of our model result, we incorporate other control variables such as population growth rate and GDP per capita. The data for this study is sourced from World Bank climate change knowledge portal and Central Bank of Nigeria Statistical Bulletin online database. Findings indicate that temperature anomaly and emissions negatively influenced food security, highlighting the urgent need for climate mitigation action. Similarly, terrorism exerts a strong negative impact on food security, stressing the need to urgently initiate policies targeted at combating the menace of terrorism in Nigeria and other developing countries. The finding from this study is imperative for government and policy analysts to adopt climate mitigation strategies aimed at reducing carbon emission in order to ensure adequate and sustainable food supply for the country’s growing population.